"Spain and the euro. The ﬁrst ten years" - Rodero Franganillo, Adolfo (Revista de Fomento Social, 2010)
Recensión de la obra de: JIMENO, Juan F. (ed.) (2010) Spain and the euro. The ﬁrst ten years, Madrid, Banco de España, 288 pp.